Towards quantitative and scalable transformation of furfural to cyclopentanone with supported gold catalysts. Issue 7 (9th December 2015) - Zhang, Gao-Shuo; Zhu, Ming-Ming; Zhang, Qi; Liu, Yong-Mei; He, He-Yong; Cao, Yong
Abstract : Coupling of small gold nanoparticles with anatase TiO2 affords by far the most selective and efficient catalytic hydrogenation system to date capable of quantitatively converting bio-derived furfural into renewable cyclopentanone in water. Abstract : Given the vital importance of furfural (FFA) upgrading towards a sustainable bio-based economy, an eco-friendly aqueous route to produce a sole valuable product from FFA is highly desirable. We herein describe an efficient approach to quantitatively convert FFA into cyclopentanone (CPO) in neat water, employing H2 as the clean reductant and supported gold nanoparticles as a simple yet versatile catalyst. The use of anatase TiO2 featuring only mild Lewis acidic sites as the underlying support is essential, not only for preventing undesirable side reactions, but also for attaining high CPO selectivity. The feasibility of using biogenic CPO and CO2 as benign carbon sources to synthesize the industrially important feedstock dimethyl adipate is also demonstrated.